Frequency of Depression among Patients with Diabetes Mellitus at PMCH Nawabshah (Medical Forum Monthly, 2024)
Objective: We will assess depressive symptoms with diabetes on diabetes self care treatment non adherence, functioning and health care.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, PMCH Nawabshah from Jan 2016 to dec 2016.Materials and Methods: 120 patients both males and females were selected for this study. We administered a Questionaire to 120 patients with type 1 and type 2 Diabetes, depressive symptoms, diabetes control, self care.Assess the impact of depressive symptoms on adherence to diabetes self care HbA1c levels functional impairment and health care.Results: 120 cases were selected, 79 were males 41 were females, 25 pts were of type 1, 95 were of type2. Depression was diagnosed using the structural clinical interview using Beck s Depression Inventory.Conclusion: Findings demonstrate association of depression with diabetes clinical consideration, treatment non adherence, proper drug treatment of diabetes, depression, self care and counseling motality can be reduced with incidence of depression.